2020
DOI: 10.1002/aocs.12412
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reaction Conditions on the Volatile Pyrazines Components of Defatted Flaxseed Meal in the Maillard Reaction System

Abstract: Defatted flaxseed meal, as a high‐protein by‐product can be used as a good raw material for the Maillard reaction (MR). A MR model system was established using glucose, fructose, and glucose/fructose (1:1) to produce volatile compounds typically obtained from defatted flaxseed meal protein hydrolysate; these compounds were analyzed using head‐space solid phase microextraction (HS‐SPME) coupled with gas chromatography‐mass spectrometry (GC–MS). From the 12 MR model reaction groups, the production of pyrazines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous studies reported that the Maillard reaction play an important role in the formation of more important nitrogen-containing heterocyclic compounds such as pyrazines, pyridines, and pyrroles (Li et al 2020 ). Pyrazines were the major nitrogen-containing compounds which contribute to the toasted, roasted, nutty, and burnt notes of cooked foods and their concentration sharply reduced from 1105.15 to 39.34 ng/g with the increasing cysteine concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the Maillard reaction play an important role in the formation of more important nitrogen-containing heterocyclic compounds such as pyrazines, pyridines, and pyrroles (Li et al 2020 ). Pyrazines were the major nitrogen-containing compounds which contribute to the toasted, roasted, nutty, and burnt notes of cooked foods and their concentration sharply reduced from 1105.15 to 39.34 ng/g with the increasing cysteine concentration.…”
Section: Resultsmentioning
confidence: 99%